Inhibition of CCCTC Binding Factor-Programmed Cell Death Ligand 1 Axis Suppresses Emergence of Chemoresistance Induced by Gastric Cancer-Derived Mesenchymal Stem Cells - Wang, Qianqian; Huang, Chao; Ding, Ying; Wen, Shaodi; Wang, Xin; Guo, Shuwei; Gao, Qiuzhi; Chen, Zhihong; Zhao, Yuanyuan; Wang, Mei; Shen, Bo; Zhu, Wei (Frontiers in Immunology, 2022)
Background Gastric cancer (GC) is the third leading cause of cancer-associated deaths worldwide. Stromal cells, especially mesenchymal stem cells (MSCs), play significant roles in the development of therapy resistance depending on their paracrine function. The PD-1/PD-L1 crosstalk between cancer and immune cells has been well studied. Emerging evidence suggests that PD-L1 also contributes to tumor resistance to therapy. Methods Cell survival and apoptosis were assessed using CCK-8, colony formation, and flow cytometry assays. Protein alterations were analyzed via western blot. Gene knockdown and overexpression were achieved with siRNA/shRNA and lentiviral infection, respectively. Drug effects on tumors in vivo were assessed with xenografts in nude mice. In addition, GC patient samples after chemotherapy treatment were collected to observe the relationship between chemotherapy effect and CTCF or PD-L1. Results In response to 5-fluorouracil or paclitaxel treatment, GCMSC-CM enhanced the cell viability and decreased the apoptosis rate. Furthermore, blocking PD-L1 or CTCF in GC cells prevented GCMSC-induced drug resistance accompanied by a decline in cell stemness. Consistent with these in vitro observations, mice treated with GCMSC-CM showed a lower sensitivity to 5-fluorouracil. In addition, high expression of CTCF and PD-L1 was associated with poor chemotherapy progression in the clinic. Conclusion Study results demonstrate a mechanism where GCMSC-CM promotes GC chemoresistance by upregulating CTCF-PD-L1 and provide strong evidence in support of targeting CTCF-PD-L1 signaling as a strategy to prevent resistance in the clinic.